The new role of temporary agency work in Germany - Alexander Spermann (Institute for the Study of Labor (IZA), 2011)
This paper reviews the development of temporary agency work after its deregulation in the context of the so-called Hartz reforms in Germany. The new role of agency work emerges from its enormous growth after deregulation, the intense use of agency work by big stock-listed companies and upcoming structural shortage of skilled labor. Agency work turns out to be procyclical and a leading indicator of labor market trends as well as an early indicator of recessions. The stepping stone hypothesis is only accepted for long-term unemployed after the Hartz reforms. Anecdotal evidence of revolving door effects is well-known but substitution as a broad-based phenomenon is not plausible. Education of staffing agents and training programs for agency workers are on the staffing industry's agenda and will be even more important in the near future due to structural skills shortages.
urn:nbn:de:101:1-201201103119
Keywords: I2; J2; J4; 330; temporary agency work; Hartz reform; staffing industry; revolving door effect; stepping stone hypothesis; Leiharbeit; Hartz-Reform; Beschäftigungseffekt; Konjunkturindikator; Personalberatung; Weiterbildung; Deutschland